Association of iron deficiency anemia with dental caries in the permanent first molars of children aged 7–12 years in Karachi, Sindh, Pakistan: protocol for an analytical cross-sectional study - Iqbal Azam; Ali Faisal Saleem; Farhan Raza Khan; Shiyam S Tikmani; Sadaf Syed; Waseem Ahmed Jamalvi (BMJ Open)
Introduction Iron deficiency anaemia (IDA) and dental caries are prevalent diseases among Pakistani children. Limited research has been done to explore their association with permanent teeth. Given the caries susceptibility of permanent first molars and their role in the development of ideal occlusion, this study aimed to estimate caries frequency in these molars and assess its association with IDA in 7–12 year-old children.Methods and analysis This analytical cross-sectional study will include 141 children aged 7–12 years visiting physicians in the paediatric OPD of Dr. Ruth K.M. Pfau, Civil Hospital Karachi. Using consecutive sampling, children who met initial screening criteria were further evaluated to determine eligibility for the study. Data collection will involve physical examinations (including weight and height), oral examinations (including the relevant oral hygiene and caries assessments) and laboratory examinations (including the prescribed tests). In addition, questions will be asked about sociodemographic characteristics, history of IDA, oral hygiene habits, smokeless tobacco use and the frequency of cariogenic dietary consumption. Exposure variable will include the presence of IDA, assessed using complete blood count, C-reactive protein and ferritin tests and treated as a dichotomous variable. Outcome variable will include dental caries in at least one permanent first molar, assessed using the Decayed, Missing, and Filled Teeth index and also treated as a dichotomous variable. Analysis will include Poisson regression with robust variance, reporting prevalence ratios with 95% CIs for the association of IDA and dental caries in the permanent first molars. Frequency of children with carious permanent first molars with 95% CIs will also be reported.Ethics and dissemination This research has been approved by ethical review committee of Aga Khan University (Reference number: 2024-9692-30593) and the institutional review board of Dow University of Health Sciences (IRB Reference: IRB-3556/DUHS/Approval/2024/196) before participant recruitment. Results will be disseminated through seminars and peer-reviewed publications.